Acute abdomen as an expression of peritoneal tuberculosis: review of the literature and a case report - Guido Nina Guida Acevedo; Rafael Martín Franco Delgado; Ximena Elizabeth Trujillo Romero (Medisur)
Tuberculosis is a common problem in the world, mainly in developing countries; Approximately 1 to 3% of all tuberculosis cases are extrapulmonary, and of these, 11 to 16% are abdominal tuberculosis, the sixth most common form. It is produced by different types of mycobacterium, the most frequent causative agent in humans being Mycobacterium tuberculosis. The aim of this article is to describe the clinical characteristics, diagnostic methods and treatment in a patient with peritoneal tuberculosis. A systematic review was carried out through various databases from the 2010 to 2022 and the clinical history corresponding to the patient studied was analyzed. Exploratory laparotomy revealed generalized granulomatous and caseous lesions in the parietal and visceral peritoneum. The histopathological study reported the presence of granulomas and acid-fast bacilli, confirming the diagnosis of peritoneal tuberculosis. Antituberculous treatment was started for six months with improvement of the condition. When faced with a patient with an acute abdomen with signs of peritoneal irritation and atypical evolution, intestinal tuberculosis should be considered as a differential diagnosis, even if there is no history of previous pulmonary involvement.